THE REDUCTION OF RETINENE(1) TO VITAMIN A(1) IN VITRO - Wald, George (The Rockefeller University Press, 1949)
In the surviving vertebrate retina the retinene(1) liberated by bleaching rhodopsin is converted quantitatively to vitamin A(1). Recent chemical studies have indicated that in this process the aldehyde group of retinene(1) is reduced to the primary alcohol group of vitamin A(1) (Morton; Wald). Some time ago we brought this reaction into a cell-free brei prepared from cattle retinas. The retinas were frozen, desiccated, ground, and exhaustively extracted with petroleum ether; the resulting powder, stirred in neutral buffer solution and exposed to light, converted its retinene(1) completely to vitamin A(1). Some time ago also we observed that fresh rhodopsin solutions exhibit a special type of fading in darkness following exposure to light, which is absent from the same solutions after aging. We have confirmed Bliss's identification of this reaction as the conversion of retinene(1) to vitamin A(1). The system which reduces retinene(1) is fractionated anatomically in the retinal rods. The outer segments of the rods, broken off from the underlying retinal tissue, are unable to convert their retinene(1) to vitamin A(1). In the presence of a water extract of crushed retina they do perform this conversion. On the other hand the retinal tissue from which a water extract was taken has lost this capacity. Such washed retinal tissue is reactivated by returning the washings to the solid material. The activating effect of retinal washings on isolated outer limbs or washed retina is duplicated by a boiled muscle juice. This in turn can be replaced by reduced cozymase (reduced coenzyme I; DPN-H(2)); or by a mixture of DPN and fructosediphosphate. The conversion of retinene(1) to vitamin A(1) is therefore a reduction in which two atoms of hydrogen are transferred to retinene(1) from reduced cozymase. It is assumed that this reaction is catalyzed by an apoenzyme, retinene(1) reductase, present in the rod outer limb. This process is coupled with a second system in the outer segment which reduces DPN, using hexosediphosphate or one of its derivatives as hydrogen donor. This action of DPN brings a member of the vitamin B complex, nicotinic acid amide, into an auxiliary position in the rhodopsin system. In the isolated retina or in vitro systems the reduction of retinene(1) proceeds irreversibly. Yet this reduction must be balanced by an oxidative process elsewhere in the rhodopsin cycle, since through rhodopsin as intermediate vitamin A(1) regenerates retinene(1).